Perilaku Prososial vs Kekerasan Sosial: Sebuah Tinjauan Pendidikan Islam - Ahmad Darmadji (EL-TARBAWI, 2011)
This paper is formulated to make a brief outlook on social violence in the perspective of Islamic education view, Indonesian culture, and al-Qur’an. Based on this perspective, this paper will discuss the root of violence behavior, whether in recent time or in the past time. This paper will also discuss pro-social behavior developed by individual as well as by society, as it becomes a counter values to violence behavior. The values found through discussion will be then introduced in an education framework as a pathway in reframing social behavior that potentially leads to violence. This action is taken due to re-comphrehend and reduce such potential ‘leads-to-violence’ behavior. The discussion presented in this paper is expected to have an inspiration for the next researches.